THE ANALYSIS OF GENDER MAINSTREAMING POLICY ON LABOR IN BANDA ACEH CITY - Cut Wita Ismail; Muhammad Nasir; Asmawati Asmawati (Syiah Kuala University, 2019)
Abstract This study aims to observe how much influence the policy of gender mainstreaming on employment in Banda Aceh city. Employment in this study is projected as the number of workers. The scope of this research is in the government of the Banda Aceh city by using SWOT analysis method. The data collected is secondary data obtained through interviews. The results of the study show that based on swot analysis there are several threats, opportunities, challenges, and weaknesses in the implementation of gender mainstreaming policies in employment in Banda Aceh city. The disadvantages are the limited willingness to work, the double burden of women as wives or mothers, lack of socialization and training, and the absence of disaggregated data. The strength of PUG policy is the Law Regulation, one of which is Presidential Instruction No. 9 of 2000, the level of education, skills, and understanding of HR.Government of Banda Aceh city should be able to support this policy through pro-gender equality programs so that there will be no gender gap in the city of Banda Aceh and One of the efforts that can be taken by the government in dealing with the issue of gender disparity is to create gender responsive programs in the form of socialization, discussion, and others that not only involve men but also women.